2018
DOI: 10.1016/j.socscimed.2018.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Why do people living with HIV not initiate treatment? A systematic review of qualitative evidence from low- and middle-income countries

Abstract: Reasons for not starting ART included consistent themes across studies. Future interventions could: (1) provide information on the large health and prevention benefits of ART and the low side effects of current regimens; (2) reduce stigma at the patient and community levels and increase confidentiality where stigma persists; (3) remove lifestyle requirements and support patients in integrating ART into their lives; and (4) alleviate economic burdens of ART. Interventions addressing reasons for non-initiation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 100 publications
(251 reference statements)
10
107
0
Order By: Relevance
“…This finding aligns with many other studies that identify health-seeking costs-long wait times, expensive transport, and lost wages-as major barriers to successful ART adherence. 3,[17][18][19] Additionally, several clients in the 6-month arm noted that reduced clinic visits improved their ability to keep their HIV status private to the community and contributed to feelings of normalcy because they were spending less time seeking health services. Benefits of decreased clinic visits also extended to the health system level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding aligns with many other studies that identify health-seeking costs-long wait times, expensive transport, and lost wages-as major barriers to successful ART adherence. 3,[17][18][19] Additionally, several clients in the 6-month arm noted that reduced clinic visits improved their ability to keep their HIV status private to the community and contributed to feelings of normalcy because they were spending less time seeking health services. Benefits of decreased clinic visits also extended to the health system level.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has identified a number of health systems and service delivery barriers to antiretroviral therapy (ART) adherence and retention in care among people living with HIV, 1,2 particularly in high-prevalence low-and middle-income countries. 3 Common challenges to delivering ART in resourcelimited settings include overburdened clinical staff and facility congestion, resulting in constrained abilities to offer quality care. 4,5 Although ART is provided free-ofcharge in many low-and middle-income countries, the need for lifelong medication imposes burdens on clients, including the time and cost of frequent refill visits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most of the patients included in our study started with lower CD4 + cell counts (<200 cells/mm 3 ), there were patients who had higher baseline CD4 + cell counts (971 cells/mm 3 ). Despite the continuous effort to initiate early, some patients still presented with lower CD4 + cell counts, which might be due to patients' lack of willingness to get tested (13,14) or difficulties to provide treatments to all patients in lower-income countries including Ethiopia. Hence, we believe that our result could be generalizable.…”
Section: Discussionmentioning
confidence: 99%